Difficulties in diagnosis and treatment of adult-onset Still's disease concurrent with pericardial effusion as a leading clinical manifestation - V. Yu. Myachikova; A. L. Maslyansky; I. Z. Gaydukova; A. N. Novikova; D. V. Karpova; E. V. Shlyakhto (Современная ревматология, 2016)
The paper considers a case of adult-onset Still's disease that occurred as acute pericarditis, two-spike hectic fever, and neutrophilic leukocytosis in a young man. It was difficult to establish a correct diagnosis because there were no characteristic clinical symptoms of Still's disease, such as salmon colored rash, arthralgia, and sore throat. The diagnosis of adult-onset Still's disease was verified on the basis of the classification criteria described by M. Yamaguchi et al. The special feature of the clinical case was the development of steroid resistance and the effective use of a combination of the interleukin-6 receptor blocker tocilizumab (8 mg/kg body weight, given intravenously dropwise once every four weeks) and methotrexate (15 mg/week orally). During this treatment, a sustained clinical and laboratory response was achieved, which could reduce the dose of glucocorticoids to the maintaining one.